Penapisan Kapang Endofit Ranting Kayu Meranti Merah (Shorea balangeran Korth.) sebagai Penghasil Enzim Xilanase - SHIRLY KUMALA; NUR ANNISA FITRI (Fakultas Farmasi Universitas Pancasila, 2008)
Endophytic microbes are microorganisms that live in the plant. These microbes, are able to produce secondary metabolites, such as oligosaccharide degrading enzymes, growth factors, antibacterial substances and Xylanaze enzyme, an enzyme that can reduce the use of chlorine as bleaching agent in paper industries. This study Was aimed to isolate endophytic fungi that can produce extracellular xylanaze. Isolation of endophytic fungi from red memnti (Shorea balangeran Korth.) branches was carried out using surface sterilization and direct seeding methods on CMM (Corn Meal Malt) medium. Xylanaze was produced by using shaking fermentation methods on PDY (Potato Dextrose Yeast) for 12 days. Enzyme activity was assessed by using DNS (Dinitro salicylic acid) method. The results showed that of nine endophytic fungi isolates, eight have xylanaze enzyme activity, ranging from 1.279 µ/ml (highest) to 0.12 µ /ml (lowest).